1989
DOI: 10.1212/wnl.39.6.762
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive slowing in Parkinson's disease fails to respond to levodopa treatment

Abstract: To evaluate clinically the slowing of cognitive processing in Parkinson's disease, we used a visual discrimination task consisting of 15 superimposed images of objects. The time needed to identify 12 objects increased by 58% in 70 patients withdrawn from levodopa treatment compared with 20 controls matched for age and education. Perceptual, motor, and psycholinguistic factors, as well as mood, only partially accounted for the slowness of performance. The 15-objects test scores of the parkinsonian patients corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…The enhancement of AC observed in our patients is consistent with the increased distractibility manifested by PD patients in the presence of irrelevant but salient stimuli, as shown in prior studies (Uc et al, 2007;Henik et al, 1993;Sharpe, 1990;Wright et al, 1990;Pillon et al, 1989). In a controlled study carried out on medicationwithdrawn PD patients performing a visuospatial memory task, behavioral and electroencephalographic measures indicated that patients were severely impaired at filtering out distractors .…”
Section: Effects Of the Disease And Of Surgery For Dbs Lead Implantationsupporting
confidence: 91%
See 1 more Smart Citation
“…The enhancement of AC observed in our patients is consistent with the increased distractibility manifested by PD patients in the presence of irrelevant but salient stimuli, as shown in prior studies (Uc et al, 2007;Henik et al, 1993;Sharpe, 1990;Wright et al, 1990;Pillon et al, 1989). In a controlled study carried out on medicationwithdrawn PD patients performing a visuospatial memory task, behavioral and electroencephalographic measures indicated that patients were severely impaired at filtering out distractors .…”
Section: Effects Of the Disease And Of Surgery For Dbs Lead Implantationsupporting
confidence: 91%
“…Finally, they are more prone to interference in the presence of a distractor stimulus compared with normal controls, as measured on a dichotic listening task (Sharpe, 1992). Moreover, several behavioral studies indicate that parkinsonian patients with overall well-preserved cognitive functions may nevertheless be impaired at a variety of visual attention tasks (Filoteo et al, 1995;Wright, Burns, Geffen, & Geffen, 1990;Yamada, Izyuuinn, Schulzer, & Hirayama, 1990) and more specifically at tasks tapping selective attention mechanisms (Cools, Rogers, Barker, & Robbins, 2009;Henik, Singh, Beckley, & Rafal, 1993;Pillon et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There is a nonlinear dose dependent effect of 6-OHDA on noradrenergic neurons, and more recent work has shown that desipramine is not needed at the lower doses of 6-OHDA used in current study (Jouve et al, 2010). Notice that even in case of minor noradrenergic degeneration following 6-OHDA injection, the animal model would be closer to human PD where same degeneration of catecholaminergic cells is likely to be associated to the pathological state (Delaville et al, 2011;Mavridis et al, 1991;Pillon et al, 1989). For control subjects (n = 8), an equal volume of vehicle (6 μl saline with 0.1% ascorbic acid) was injected.…”
Section: -Hydroxydopamine Lesion Of the Sncmentioning
confidence: 83%
“…Unclear results emerged from previous studies exploring the effect of L-dopa administration on WM-related cognitive functioning in PD patients. Some investigators reported performance improvement of WM tasks after L-dopa treatment [27,43,44] while others did not find any effect [45] or found a slowing effect [46] of L-dopa on the cognitive processing speed of these patients. These contrasting results may be partially explained by the clinical heterogeneity of the different PD patient groups examined and by the different methodological procedures used.…”
Section: Discussionmentioning
confidence: 96%